PENGARUH POLA PIKIR TRADISIONAL TERHADAP RENDAHNYA KESADARAN PENDIDIKAN MASYARAKAT DESA KANEGARAH KECAMATAN KONANG KABUPATEN BANGKALAN - Behrowi Behrowi; M. Sahid (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the influence of traditional mindset on the low educational awareness of the community in Kanegarah Village, Konang District, Bangkalan Regency. Methods: This research employs a qualitative descriptive approach. Data were collected through in-depth interviews with five informants representing diverse backgrounds: students, university students, youth who dropped out of school, parents, and village officials. Observation and documentation were also utilized as supporting instruments. Data analysis followed Miles and Huberman's interactive model, encompassing data reduction, data display, and conclusion drawing, with triangulation employed to ensure data credibility. Results: The findings reveal three main conclusions. First, traditional mindset significantly influences low educational awareness, manifested through the belief that formal education provides no direct economic benefit, the perception that basic literacy skills are sufficient, and the prioritization of work over schooling. Second, the community's educational awareness level remains categorized as low to moderate, characterized by minimal continuation to higher education levels, insufficient parental support for children's learning, and low intrinsic motivation among students. Third, several strategies are identified as effective for improving educational awareness, including intensive socialization programs for parents, empowerment of community and religious leaders as change agents, expansion of targeted scholarship access, strengthening the school's role in community engagement, and integration of educational values into local cultural traditions. Novelty: This study contributes new insights into the specific socio-cultural dynamics of Madurese society in Kanegarah Village, providing an empirically grounded understanding of how traditional mindset operates as a structural barrier to educational advancement in rural Indonesian communities.